"I Don't Want to Come Off as Pushing an Agenda": How Contexts Shaped Teachers' Pedagogy in the Days After the 2016 U.S. Presidential Election. (April 2019) - Dunn, Alyssa Hadley; Sondel, Beth; Baggett, Hannah Carson
Guided by perspectives on the sociopolitical contexts of schooling, control of teachers' curriculum and instruction, and teaching of elections, we use findings from a national questionnaire to explore the contexts that shaped teachers' pedagogical decision making following the 2016 U.S. presidential election. Our findings reveal that classroom, school, district, state, and national contexts often manifested in pressure from colleagues, parents, the administration, the district, and the public. This pressure is reflective of the lack of trust, autonomy, and professionalism for teachers in our current climate. The days immediately following the election revealed new understandings about teachers' views on neutrality, opportunities for agency within control of teachers' work, and a call for justice-oriented pedagogy. Implications for teacher education, practice, and research are discussed.